An independent audit oversight system in a developing country - Mustapha, Mazlina; Lim, Yan Kong (Editorial Universidad de Almería, 2021)
Audit Oversight Board (AOB) was established in Malaysia to regulate the auditors of public listed companies and instil the trust and confidence of the public on the quality of audit services provided by them. This study aims to explore the impact of AOB establishment on external auditors. Interviews were conducted with twenty audit seniors and managers in Big four and non-Big four firms in Klang Valley. The interviews revealed that more works were done and more documentation was compiled after AOB establishment. The results also indicated that more informal meetings were conducted to get more information and clarification from the clients to solve audit issues. However, the auditors claimed that their reliance on the internal auditors was not affected by AOB establishment. The findings also suggested that audit fee was not directly affected by the establishment of AOB. The results of the study contribute to the literature and understanding of AOB establishment in Malaysian audit industry.